The law of Ukraine «On protection of personal data»: problems and ways to improve - Червякова, О. Б. (Problems of legality, 2013)
This article analyzed and studied the individual provisions of the law of confidentiality of personal citizens in terms of their safety and protection. Particular attention is paid to the improvement of the legal framework of citizens’ rights in this area.